Manajemen Kurikulum Pendidikan Agama Islam Berbasis Ulumul Qur'an - Susiyati; Ririn Septika Fitri; Nilna Fadlillah; Saripah Aini (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This article discusses the management of Islamic religious education curriculum based on Ulumul Qur'an, with a focus on the development and implementation of an effective curriculum in educational institutions. This study aims to describe the curriculum management process including planning, organizing, implementing, and evaluating, and how the principles of Ulumul Qur'an can be integrated into each stage of management. Through a qualitative approach, data were collected through observation, interviews, and documentation in several madrasahs. The results of the study indicate that the implementation of good curriculum management can improve the quality of Islamic religious education, shape students' characters in accordance with Qur'anic values, and prepare them to face global challenges. This article also identifies supporting and inhibiting factors in curriculum management based on Ulumul Qur'an, and provides recommendations for further development in the context of Islamic religious education. Thus, this study is expected to make a significant contribution to improving the quality of Islamic religious education in Indonesia.